Leaving Distress Behind: A Randomized Controlled Study on Change in Emotional Processing in Borderline Personality Disorder. Issue 2 (3rd April 2017) - Berthoud, Laurent; Pascual-Leone, Antonio; Caspar, Franz; Tissot, Hervé; Keller, Sabine; Rohde, Kristina B.; de Roten, Yves; Despland, Jean-Nicolas; Kramer, Ueli
Abstract : Objective : The marked impulsivity and instability of clients suffering from borderline personality disorder (BPD) greatly challenge therapists' understanding and responsiveness. This may hinder the development of a constructive therapeutic relationship despite it being of particular importance in their treatment. Recent studies have shown that using motive-oriented therapeutic relationship (MOTR), a possible operationalization of appropriate therapist responsiveness, can enhance treatment outcome for BPD. The overall objective of this study is to examine change in emotional processing in BPD clients following the therapist's use of MOTR. Method : The present paper focuses on N  = 50 cases, n  = 25 taken from each of two conditions of a randomized controlled add-on effectiveness design. Clients were either allocated to a manual-based psychiatric-psychodynamic 10-session version of general psychiatric management (GPM), a borderline-specific treatment, or to a 10-session version of GPM augmented with MOTR. Emotional states were assessed using the Classification of Affective-Meaning States (Pascual-Leone & Greenberg, 2005) at intake, midtreatment, and in the penultimate session. Results : Across treatment, early expressions of distress, especially the emotion state of global distress, were shown to significantly decrease ( p  = .00), and adaptive emotions were found to emerge ( p  < .05). Between-condition differences of change were found, including a significant increase in emotional variability and stronger outcome predictors in the MOTR condition. Conclusions : The findings indicate initial emotional change in BPD clients in a relatively short time frame and suggest the addition of MOTR to psychotherapeutic treatments as promising. Clinical implications are discussed.